Design of Electrical Energy Power System Based on Wind Turbine and Solar Panel - Maulana, Frendi; Mutmainah, Siti (Institut Teknologi Dirgantara Adisutjipto, 2019)
This research aims to develop the design of wind-solar power plants in shrimp pond areas. The prototype was developed according to the design of the generator made. Design efficiency is demonstrated by analyzing electrical energy generated in the system. The methods include: build generator system design, prototype assembly and testing. The design developed is to maximize work of the radial generator system through manufacturing of rotors with neodymium magnets. The test results obtained an average battery charging of 29.72 watts. The lowest solar intensity occurs at 06.00 WIB (46300 lumens). While the highest intensity occurred at 14.00 WIB (116200 lumens). The highest wind speed of 2.8 m/s at 12:00 WIB. This clarifies that the intensity of the sun and wind speed affect the value of battery, the value will be directly proportional that the greater the intensity and speed, the greater electrical energy produced.